Survival of Pseudomonas aeruginosa in M-K preserved corneas. Issue 6 (27th May 2005) - Panda, A; Satpathy, G; Sethi, H S
Abstract : Aim: To present seven eyes of suspected donor to host transmitted Pseudomonas sp corneal graft infection after corneal and scleral graft leading to corneal melting within 24 hours, in a span of 10 months. Methods: Case series. Seven eyes, operated for either penetrating or lamellar keratoplasty or scleral patch graft for different indications and which developed massive corneal/corneoscleral infection within 24 hours, were studied prospectively. Results: Pseudomonas aeruginosa, resistant to almost all antibiotics except polymyxin B in all and vancomycin in two, was identified as the causative organism from all the specimens obtained from the infected graft. Conclusion: Post-keratoplasty infection is a disaster. The source of early infection is invariably iatrogenic. Use of empirical antibiotics in the media is not always sufficient to prevent such infection. Thus, measures must be taken in the form of strict maintenance of asepsis and revision of antibiotics added to the storage medium. Further, early recognition and energetic therapy for such infection could reduce the ophthalmic morbidity.